Tumors defective in homologous recombination rely on oxidative metabolism: relevance to treatments with PARP inhibitors. Issue 6 (13th May 2020) - Lahiguera, Álvaro; Hyroššová, Petra; Figueras, Agnès; Garzón, Diana; Moreno, Roger; Soto‐Cerrato, Vanessa; McNeish, Iain; Serra, Violeta; Lazaro, Conxi; Barretina, Pilar; Brunet, Joan; Menéndez, Javier; et al.
Abstract: Mitochondrial metabolism and the generation of reactive oxygen species (ROS) contribute to the acquisition of DNA mutations and genomic instability in cancer. How genomic instability influences the metabolic capacity of cancer cells is nevertheless poorly understood. Here, we show that homologous recombination‐defective (HRD) cancers rely on oxidative metabolism to supply NAD + and ATP for poly(ADP‐ribose) polymerase (PARP)‐dependent DNA repair mechanisms. Studies in breast and ovarian cancer HRD models depict a metabolic shift that includes enhanced expression of the oxidative phosphorylation (OXPHOS) pathway and its key components and a decline in the glycolytic Warburg phenotype. Hence, HRD cells are more sensitive to metformin and NAD + concentration changes. On the other hand, shifting from an OXPHOS to a highly glycolytic metabolism interferes with the sensitivity to PARP inhibitors (PARPi) in these HRD cells. This feature is associated with a weak response to PARP inhibition in patient‐derived xenografts, emerging as a new mechanism to determine PARPi sensitivity. This study shows a mechanistic link between two major cancer hallmarks, which in turn suggests novel possibilities for specifically treating HRD cancers with OXPHOS inhibitors. Synopsis: Homologous recombination‐defective (HRD) cancers need high levels of NAD + and ATP for alternative PARP‐dependent DNA repair. HRD cancer cells undergo a characteristic metabolic shift that include enhanced OXPHOS, opening new opportunities for treatment with OXPHOS inhibitors like metformin. Studies in different cancer BRCA‐mutated models depict a metabolic shift that includes enhanced expression of the oxidative phosphorylation (OXPHOS) pathway and a decline in the glycolytic Warburg phenotype. HRD cancers rely on oxidative metabolism to supply NAD + and ATP for Poly (ADP‐ribose) polymerase (PARP)‐dependent DNA repair mechanisms. In consequence HRD tumors are more sensitive to OXPHOS inhibitors, such as metformin, and NAD + concentration changes. Moreover, shifting from an OXPHOS to a highly glycolytic metabolism interferes with the sensitivity to PARP inhibitors (PARPi) in these HRD cells. Abstract : Homologous recombination‐defective (HRD) cancers need high levels of NAD + and ATP for alternative PARP‐dependent DNA repair. HRD cancer cells undergo a characteristic metabolic shift that include enhanced OXPHOS, opening new opportunities for treatment with OXPHOS inhibitors like metformin.